2022
DOI: 10.1007/s10826-022-02344-8
|View full text |Cite
|
Sign up to set email alerts
|

Good Traits, Bad Traits, and ‘Ugly’ Behavior: Relations between the Dark Triad, Honesty-Humility, Other HEXACO Personality Traits, and Externalizing Problems in Adolescents

Abstract: The present study investigated the relative contributions of the Dark Triad, honesty-humility, and other HEXACO traits to externalizing problems in young people. One-hundred-and-six adolescents aged between 12 and 18 years completed an online survey containing the Dirty Dozen for Youth as an index of the Dark Triad traits of psychopathy, Machiavellianism, and narcissism, the HEXACO-Middle School Inventory to assess honesty-humility as well as five other basic personality factors, and the Youth Self-Report to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 68 publications
2
11
0
1
Order By: Relevance
“…Psychopathy is characterized by low effect (suggesting lower Emotionality), a tendency to use violence and intimidation (suggesting low Agreeableness), avoidance of responsibility (low Conscientiousness), and a tendency to exploit or take advantage of others (low Honesty-Humility). Previous research supports these theoretical links, and we expected to further replicate these results (Book et al, 2015(Book et al, , 2016Mularczyk et al, 2020;Muris et al, 2022).…”
Section: Predictionssupporting
confidence: 57%
See 2 more Smart Citations
“…Psychopathy is characterized by low effect (suggesting lower Emotionality), a tendency to use violence and intimidation (suggesting low Agreeableness), avoidance of responsibility (low Conscientiousness), and a tendency to exploit or take advantage of others (low Honesty-Humility). Previous research supports these theoretical links, and we expected to further replicate these results (Book et al, 2015(Book et al, , 2016Mularczyk et al, 2020;Muris et al, 2022).…”
Section: Predictionssupporting
confidence: 57%
“…Normative personality has long been studied using models such as the Big Five that provide insight into the structure and conceptualization of traits that might be considered "abnormal". Indeed, this method has allowed for a better understanding of a variety of problematic personality traits and the ways in which they overlap (Book et al, 2015(Book et al, , 2016Hilbig et al, 2020;Miller et al, 2001;Miller & Lynam, 2015;Mularczyk et al, 2020;Muris et al, 2022). The Big 5 comprised five factors: Openness to experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism.…”
Section: Intersection With Basic Personality Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…personality disorder (Miskewicz et al, 2022;Thielmann et al, 2014), and externalizing disorders such as oppositional defiant disorder and conduct disorder (Muris et al, 2022). A PsycINFO search indicated that since 2000, there have been over 2,700 citations to the HEXACO model, with the greatest number of citations in the past 5 years.…”
mentioning
confidence: 99%
“…The honesty–humility scale is particularly useful in the study of antagonistic personality traits and disorders (Book et al, 2015). As a result, the HEXACO has been applied to research examining psychopathy (Marcus et al, 2019; Ruchensky & Donnellan, 2017), narcissism (Bresin & Gordon, 2011), borderline personality disorder (Miskewicz et al, 2022; Thielmann et al, 2014), and externalizing disorders such as oppositional defiant disorder and conduct disorder (Muris et al, 2022). A PsycINFO search indicated that since 2000, there have been over 2,700 citations to the HEXACO model, with the greatest number of citations in the past 5 years.…”
mentioning
confidence: 99%